The Principle of Common but Differentiated Responsibilities (CBDR): The Future of Climate Justice: https://doi.org/10.5281/zenodo.17821510 - Dr. Abida Abdul Khaliq; Sijal Zafar; Muhammad Ahsan Iqbal Hashmi (Corresponding Author) (`, 2025)
The Common but Differentiated Responsibilities (CBDR) principle is one of the foundations of international environmental laws, as it constitutes the pragmatic flexibility as well as the moral equality in the international approach to the issue of climate change. CBDR, based on the understanding that although every state will have a role in protecting the environment, the need of each country to limit its carbon emissions varies, based on its historical emissions, capacity, and developmental priorities, has led the international environmental negotiations since the 1992 Rio Earth Summit. However, the changing climate regime, especially when it comes to the Paris Agreement, has brought forth contradictions between differentiation and universality. This paper will discuss the legal, ethical, and political basis of CBDR, how it has been modified by the consecutive climate treaties, and how it can play out in the future in regards to climate justice. It will argue, based on historical background, treaty interpretation, and the literature, that CBDR should be transformed into a dynamic differentiation model, which guarantees equity without deterring a common world ambition. Keywords: Common but Differentiated Responsibilities (CBDR); Climate Justice; International Environmental Law; Paris Agreement; Climate Governance; North–South Divide; Equity; Global Climate Finance.